A Web-Based Boarding House Information System in Yogyakarta - Rachmadi, Andry; Asyhab, Naufal; Fauzi, Muhammad Dzulfikar; Mulyanto, Agus (IJID (International Journal on Informatics for Development), 2016)
Daerah Istimewa (Special Region of) Yogyakarta has 3,186 km2 wide area with 3,020,837 populations. Yogyakarta is well-known as an education city and a new student destination. Until 2005, it was reached number of 229,761 students (DIY Education Department, 2006). Finding boarding houses which are as needed and desired by students and learners is not easy. The obstacle that is often faced is do not know the area, or do not have friends who can give suggestion of appropriate boarding houses for students and learners. Therefore, it is necessary to create boarding house information system to facilitate students when looking for a place to stay. This information system is expected to help students finding a boarding house and also help boarding house owners to publish an empty boarding house room. System development method in this study is SDLC (System Development Life Cycle) using a waterfall model. The waterfall model is a systematic approach and sequential starting of the level of system requirements, then to the analyzing data, designing, coding, and testing / verification. The boarding house information system is capable of informing the boarding line with the criteria sought by searchers. This information system is also capable of displaying the boarding house location utilizing Google Maps API to ease the boarding house location searching.